2010
DOI: 10.1016/j.ehrm.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Vermont Diabetes Information System on Inpatient and Emergency Department Use: Results from a Randomized Trial

Abstract: Objective-To describe the effect of the Vermont Diabetes Information System (VDIS) on hospital and emergency room use Data Source-Statewide discharge databaseStudy Design-Randomized controlled trial of a decision support system for 7,412 adults with diabetes and their 64 primary care providers.Data Collection/ Data Extraction-Charges and dates for hospital admissions and emergency room care in Vermont during an average of 32 months of observation. Data from New York hospitals were not available.Principal Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Three studies only showed improvements in the process of care. Improvements were found in yearly HbA1c testing, retinal exams, and the composite of three tests, as well as in laboratory monitoring, 18 low-density lipoprotein testing, and the composite of all Cleveringa et al, [15][16][17] Phillips et al 14 and Ziemer et al, 6 and MacLean et al 19 and Khan et al 18 represent the same respective study with different outcome parameters. a Value in randomized column is 1 if patients were randomized or when cluster randomization with the generalized estimating equation (GEE) was used.…”
Section: Effectiveness Of a Cdss Alone (Table 2)mentioning
confidence: 95%
See 1 more Smart Citation
“…Three studies only showed improvements in the process of care. Improvements were found in yearly HbA1c testing, retinal exams, and the composite of three tests, as well as in laboratory monitoring, 18 low-density lipoprotein testing, and the composite of all Cleveringa et al, [15][16][17] Phillips et al 14 and Ziemer et al, 6 and MacLean et al 19 and Khan et al 18 represent the same respective study with different outcome parameters. a Value in randomized column is 1 if patients were randomized or when cluster randomization with the generalized estimating equation (GEE) was used.…”
Section: Effectiveness Of a Cdss Alone (Table 2)mentioning
confidence: 95%
“…13 The study from Phillips et al 14 and Ziemer et al 6 regarded the same study population, with different outcome measures. This also applies to the three studies of Cleveringa et al [15][16][17] and to the studies from Khan et al 18 and MacLean et al 19 Therefore eventually 20 RCTs were included. Ninety-five articles were excluded because of different reasons, for example, review article (n = 14), no RCT (n = 22), no CDSS used in the intervention (n = 26), glucose monitoring system (n = 10), or diabetes self-management program (n = 11) (Fig.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Economic Outcomes.-Three studies reported economic outcomes, namely Bates et al, 25 Smith et al, 21 and Khan et al 29 Bates et al 25 reported the possible charge savings when implementing a CCDSS that reminds a physician upon ordering a new test that the same test had already been ordered within certain test-specific intervals. They calculated that the 24% decrease in test ordering correlated to a $35 000 annual savings for the clinic.…”
Section: 10])mentioning
confidence: 99%
“…46,47 Thirteen studies (57%) evaluated CCDSSs in primary care,* 5 (22%) in hospital outpatient ambulatory care, 26,31,33,36,44 and 5 (22%) in hospital inpatient care. 22,25,32,34 Intervention.-Fifteen different CCDSSs were studied, of which 6 (40%) were focused solely on laboratory testing, † 5 (33%) also included other reminders such as treatment options, [27][28][29]31,39,[41][42][43] and 4 (27%) were not stand-alone systems, but were developed by an EHR software vendor. ‡ Of the CCDSSs focused solely on laboratory testing, 3 (50%) were targeted at regulating blood clotting in patients using anticoagulants.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation